HIV testing and self-reported HIV status in South African men who have sex with men: results from a community-based survey. Issue 6 (21st November 2008) - Sandfort, T G M; Nel, J; Rich, E; Reddy, V; Yi, H
Abstract : Objective: To investigate the characteristics of South African men who have sex with men (MSM) who (1) have been tested for HIV and (2) are HIV positive. Methods: Data were collected from 1045 MSM in community surveys using questionnaires that were administered either face-to-face, by mail or on the internet. The mean age of the men was 29.9 years. The race distribution was 35.3% black, 17.0% coloured, 5.3% Indian and 41.1% white. Results: The proportion of MSM tested for HIV was 69.7%; having been tested was independently associated with being older, being more open about one's homosexuality and being homosexually instead of bisexually attracted; black MSM, students and MSM living in KwaZulu-Natal were less likely to have been tested. Of the 728 MSM who had been tested, 14.1% (n = 103) reported to be HIV positive (9.9% of the total sample). Being HIV positive is independently associated with two factors: men who were positive were more likely to have a lower level of education and to know other people who had HIV/AIDS; race was not independently associated with HIV status among those who had been tested. Conclusions: The likelihood of having been tested for HIV seems to decrease with increasing social vulnerability. Racially, the distribution of HIV among MSM seems to differ from that of the general South African population, suggesting that while intertwined with the heterosexual epidemic there is also an epidemic among South African MSM with specific dynamics. These findings suggest that in-depth research is urgently needed to address the lack of understanding of HIV testing practices and HIV prevalence in South African MSM.